Interactive Effects of Soil Type and Chicken Manure Dosage on the Growth and Soil Response of Curly Lettuce (Lactuca sativa L.) - Eggye Andrew Sebayang; Amir Noviyanto; Retni Mardu Hartati (BPFP Universitas Bengkulu, 2025)
Andosols and Latosols are widely distributed tropical soils with distinct limitations for horticultural production. Andosols, despite their high porosity and water retention, often exhibit phosphorus fixation and structural instability, while Latosols are characterized by low nutrient reserves and poor cation exchange capacity due to intense weathering. Addressing these constraints, this study investigates the interactive effects of chicken manure fertilizer dosage and soil type on the growth performance of curly lettuce (Lactuca sativa L. var. crispa), aiming to enhance crop productivity and soil quality through organic input management. A factorial experiment was conducted from February to March 2025 at INSTIPER Yogyakarta (118 m asl), using a Completely Randomized Design (CRD) with two factors: soil type (Andosols and Latosol) and chicken manure dosage (0 g, 250 g, 500 g, and 750 g per polybag). Each of the 8 treatment combinations was replicated three times, with two plants per replication, totalling 48 experimental units. Growth parameters measured included plant height, leaf number, shoot and root biomass, and leaf area index, while post-harvest soil analyses evaluated moisture content, pH, organic carbon, total nitrogen, and physical properties. Data were analysed using ANOVA and Duncan’s Multiple Range Test at a 5% significance level. Results demonstrated a significant interaction between soil type and manure dosage on leaf number and fresh shoot weight. The optimal growth response was observed at the 500 g dosage in Andosols, indicating improved nutrient availability and organic matter contribution. Chicken manure also enhanced soil fertility by increasing organic carbon and total nitrogen, especially in Andosols. The study provides novel evidence that tailored organic fertilization can mitigate inherent soil limitations in tropical agroecosystems, promoting sustainable lettuce production through integrated soil fertility management. Full text pdf